Ameliorative effects and histological assessment of active fractions of ethanolic fruits extract of Raphia hookeri on AlCl3 induced toxicity in rats - Eje Yakubu, Ojochenemi; Akighir, John; Imo, Chinedu; Akaangee, Lukas De Jesus; Shaibu, Isaac Eleojo; Owuna, Reuben (International Journal of Advances in Medicine, 2024)
Background: Aluminium chloride is a widely distributed element with a well-established toxicity. The study aimed at evaluating ameliorative effects of active fractions and ethanolic fruits extracts of Raphia hookeri on AlCl3-induced toxicity in male rats. The objectives included; determination of liver and kidney function biomarkers, lipid profile, histopathological assessment of the organs. Methods: A total of 110 healthy male rats weighing 180-200 g were grouped into 11 groups of 10 rats each. Group 1: Normal feed and water (normal control). Group 2: AlCl3 only. Group 3: 200 mg/kg b. w of vitamin C. Group 4 and 5: N-hexane fraction at 10 and 20 mg/kg b. w. Group 6 and 7: ethyl acetate fraction at 10 and 20 mg/kg b. w. Group 8 and 9: Aqueous fractions at 10 and 20 mg/kg b. w. Group10 and 11: Ethanol extract at doses of 200 mg/kg b. w and 400 mg/kg b. w. The treatment lasted for 21 days. Results: Results revealed a significant (p˂0.05) decreased in the activities of ALT, AST, ALP, TB, DB and TP. It further revealed a significant (p˂0.05) decrease in urea, creatinine, sodium, potassium and chloride. Also, a significant (p˂0.05) decrease in CHOL, TG, HDL-C, LDL-C was observed. Histopathological assessment of the liver and kidney tissues corroborated the observed changes in enzymes activities. Conclusions: The findings demonstrated ameliorative potentials of active fractions and ethanolic fruit extract of Raphia hookeri against hepatic and renal damage induced by AlCl3 in a dose and time dependent manner.